2016
DOI: 10.1177/2153368716645842
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Sources of Racial Bias in Potentially Capital Cases

Abstract: While prior research has uncovered racial disparities in the administration of death sentences, little attention has been devoted to earlier stages in the capital punishment processes. To understand the locus of racial bias within death penalty institutions, this study examines the entry of homicide cases into Los Angeles County's criminal justice system during a 5-year period. This two-part analysis seeks to answer the following research questions: (1) Does victim/defendant race influence homicide clearance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 73 publications
2
31
0
Order By: Relevance
“…Finally, this study’s data limited it to a focus exclusively on the capital sentencing process, as such it overlooked a great deal of potentially critical discretion at several junctures earlier in the processing of these capital cases; key among these are the prosecutors’ decisions to seek the death penalty and, if so, which aggravating circumstances to present (see, Paternoster, 1983; Petersen, 2016; Radelet & Pierce, 1985; Sorensen & Wallace, 1999). Our observation of racial disparity in the sentencing rape-involved capital murder cases may mask and/or may be due, in part, to these more systemic disparities that are present at these earlier stages of case processing.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study’s data limited it to a focus exclusively on the capital sentencing process, as such it overlooked a great deal of potentially critical discretion at several junctures earlier in the processing of these capital cases; key among these are the prosecutors’ decisions to seek the death penalty and, if so, which aggravating circumstances to present (see, Paternoster, 1983; Petersen, 2016; Radelet & Pierce, 1985; Sorensen & Wallace, 1999). Our observation of racial disparity in the sentencing rape-involved capital murder cases may mask and/or may be due, in part, to these more systemic disparities that are present at these earlier stages of case processing.…”
Section: Discussionmentioning
confidence: 99%
“…While Gross and Mauro (1984) reported Black offenders to be more likely to be sentenced to death, other studies did not find an effect of offender race on sentence severity (Baumer & Martin, 2013;Curry, 2010;Glaeser & Sacerdote, 2003). Similarly, while some authors reported Hispanic offenders to be more likely to receive harsher sentences (Auerhahn et al, 2017), others (Petersen, 2017a) found the opposite.…”
Section: Results Of Individual Studiesmentioning
confidence: 97%
“…In a separate analysis of prosecutorial decisions to seek the death penalty, the race of the victim was also taken into consideration in cases of a midrange severity (Baldus et al, 1985). More recently, a study of capital cases also examined whether the race of the victim affects if a case is cleared and whether the defendant receives a capital charge (Petersen, 2017). They found that cases involving Latino victims had lower clearance rates and the defendants were less likely to be charged with a capital offense.…”
Section: The Court Processing Of Homicide Offendersmentioning
confidence: 99%